Multifunctional superhydrophobic coatings fabricated from basalt scales on a fluorocarbon coating base. (10th September 2021) - Zheng, Hongpeng; Liu, Li; Meng, Fandi; Cui, Yu; Li, Zhong; Oguzie, Emeka E.; Wang, Fuhui
Graphical abstract: Highlights: The mesoporous etched basalt scales were synthesized by chemical etching. The etched basalt scales were fluorinated to reduce the surface energy. A multifunctional superhydrophobic coating was prepared by spraying. The coating exhibits UV-durability, anticorrosive and antibacterial abilities. Abstract: Superhydrophobic coatings are increasingly being evaluated as anticorrosion interventions in exceedingly hydrated environments. However, concerns about their long-term durability and amenability to large-area applications in marine environments are still hindering commercial-scale deployment. This study is focused on development of easy-to-apply superhydrophobic coatings, with multifunctional capabilities, in order to extend the integrity and durability of the coatings in harsh marine environments. Here, a set of facile methods involving selective chemical etching using concentrated NaOH, as well as fluorination with perfluoropolyether methyl ester were adopted to fabricate a superhydrophobic surface on basalt scales, having the required rough hierarchical micro-nanotextured and low surface energy. The superhydrophobic basalt scales were subsequently aligned atop a fluorocarbon resin, pre-deposited on a metal substrate, to yield a multifunctional superhydrophobic coating (3 μL water droplet; contact angle = 165.1°, rolling angle = 0.7°), easily amenable to large surface area application and having excellent wear resistance, UV-aging resistance, salt spray resistance, corrosion resistance and antibacterial capabilities.